2010
DOI: 10.2464/jilm.60.237
|View full text |Cite
|
Sign up to set email alerts
|

Texture randomization of AZ31 magnesium alloy sheet for improvement of cold formability by combination of rolling and high temperature annealing

Abstract: To improve the cold formability of AZ31 magnesium alloy sheets, we investigate texture control by rolling and annealing. The texture ideal for forming close to random orientation was obtained by annealing at 773 K before and after isothermal rolling at 298-573 K. For the randomizing process, such a high temperature in pre-annealing was essential, whereas a slightly lower temperature was acceptable for final annealing, assuming a sufficiently long annealing time. The randomized sheet could be obtained in a wide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…3 shows the (0002) pole figure of each sample analyzed by X-ray diffraction. The as-rolled sheet exhibits a texture with the basal plane parallel to the sheet plane, which is a typical texture reported for the rolled magnesium alloys [1,3]. Compared to the as-rolled sheets, FAEed sheets indicate the basal plane inclined by about 15˚ against the ED at all extrusion temperatures.…”
Section: Resultsmentioning
confidence: 55%
See 1 more Smart Citation
“…3 shows the (0002) pole figure of each sample analyzed by X-ray diffraction. The as-rolled sheet exhibits a texture with the basal plane parallel to the sheet plane, which is a typical texture reported for the rolled magnesium alloys [1,3]. Compared to the as-rolled sheets, FAEed sheets indicate the basal plane inclined by about 15˚ against the ED at all extrusion temperatures.…”
Section: Resultsmentioning
confidence: 55%
“…In general, it is known that a texture in which the basal plane in the hexagonal close packed structure is parallel to the sheet plane develops in magnesium alloy sheets produced by rolling or extrusion [1,2]. However, since the active slip system of magnesium alloy at room temperature is limited to basal slip, the development of such texture deteriorates sheet formability like bulging and deep-drawing [3]. For this reason, many magnesium alloy parts are manufactured by casting methods such as die casting and thixomolding [4].…”
Section: Introductionmentioning
confidence: 99%
“…Hence, research on texture randomization has also been conducted. 2) Although several studies have been carried out on the formation mechanism of basal texture by hot rolling, the mechanism has not been clarified enough. 3) Two of the authors studied the formation behavior of textures in AZ31 and AZ61 magnesium alloys under high temperature uniaxial compression deformation and found that the degree of texture development and the main component changed during dynamic recrystallization with the deformation conditions.…”
Section: Introductionmentioning
confidence: 99%